2003
DOI: 10.1177/155005940303400305
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Electroencephalographic Studies of Cue-Induced Cocaine Craving

Abstract: Quantitative electroencephalographic (qEEG) profiles were studied in cocaine dependent patients in response to cocaine cue exposure. Using neurometric analytical methods, the spectral power of each primary bandwidth was computed and topographically mapped. Additional measures of cue-reactivity included cocaine craving, anxiety and related subjective ratings, and physiological measures of skin conductance, skin temperature, heart rate, and plasma cortisol and HVA levels. Twenty-four crack cocaine-dependent subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 45 publications
3
38
2
Order By: Relevance
“…In contrast, Knott et al [23] found delta activity to be decreased in response to urge-related imagery, but only in males. Alpha activity remained unaffected by urge and no-urge scripts and drug-related stimuli in both smokers and cocaine users [23,24] .…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, Knott et al [23] found delta activity to be decreased in response to urge-related imagery, but only in males. Alpha activity remained unaffected by urge and no-urge scripts and drug-related stimuli in both smokers and cocaine users [23,24] .…”
mentioning
confidence: 93%
“…During active cocaine paraphernalia handling and video viewing only beta activity was enhanced. Changes in delta power were more dependent on task: during imagery, there was an increase in delta, whereas a drop was observed in the paraphernalia and video task [24] . In contrast, Knott et al [23] found delta activity to be decreased in response to urge-related imagery, but only in males.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Firstly, our data are in accordance with studies on cocaine in humans. For example, a reduction in delta power in the frontal cortex during touching and seeing cocaine cues has been observed, suggestive of craving, while an increase was found during guided imagery of cocaine, indicative of analogical reward (Reid et al, 2003). Cocaine also produced an increase in delta coherence over the prefrontal cortex, indicating the involvement of delta activity in the rewarding properties of cocaine (Reid et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory conditions drug-related cues are used to elicit craving and to examine neurophysiological substrates of cue-elicited craving (Bonson et al, 2002;Ehrman et al, 1992Ehrman et al, ,1998Franken, 2003;Robbins et al, 1997). Studies are reported on neuroimaging , Garavan, Ross, & Stein, 1999Kilts et al, 2004), EEG (Bauer & Kranzler, 1994;Liu et al, 1998;Reid et al, 2003) and autonomic (Robbins et al, 1999;Ingjaldsson et al, 2003) effects associated with drug cue-related responses and craving.…”
Section: Cue Reactivity and Craving: Subjective And Psychophysiologicmentioning
confidence: 99%